2009
DOI: 10.1111/j.1365-2095.2008.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nutrition of hybrid striped bass (Morone chrysops × M. saxatilis) bioavailability, toxicity and interaction with vitamin E

Abstract: Two concurrent 12‐week feeding trials were conducted to evaluate the bioavailability of inorganic sodium selenite and organic seleno‐DL‐methionine and to investigate the potential interaction between selenium and vitamin E in juvenile hybrid striped bass. In experiment 1, purified diets utilizing casein, gelatin and an amino acid premix as protein sources with a basal selenium concentration of 0.11 mg Se kg−1 were supplemented with either Na2SeO3 to provide selenium concentrations of 1.19, 2.00, 5.17 and 21.23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
7
50
0
3
Order By: Relevance
“…Differences in sources of selenium, especially as related to its absorption (which is directly linked to selenium's physical and chemical form), can greatly impact animal physiological function. However, recent studies have shown that organic forms like selenomethionine or selenium obtained from yeast improve growth and increase enzyme activity in the antioxidant system [16,46]. Selenite improved growth and GPx activity more than selenomethionine for cobia (Rachycentron canadum L [47]).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in sources of selenium, especially as related to its absorption (which is directly linked to selenium's physical and chemical form), can greatly impact animal physiological function. However, recent studies have shown that organic forms like selenomethionine or selenium obtained from yeast improve growth and increase enzyme activity in the antioxidant system [16,46]. Selenite improved growth and GPx activity more than selenomethionine for cobia (Rachycentron canadum L [47]).…”
Section: Discussionmentioning
confidence: 98%
“…However, obvious linear relationships between tissue Se accumulation and dietary Se concentrations have been reported in rainbow trout (Hilton et al 1980;Ku¨c¸u¨kbay et al 2009), grouper (Lin & Shiau 2005), African catfish (AbdelTawwaba et al. 2007) and hybrid striped bass (Jaramillo JR et al 2009). Lorentzen et al (1994) suggested that highest concentrations of Se were found in kidney and liver, which are known target organs of Se metabolism.…”
Section: Selenium Is An Essential Element For Fish (Hamilton 2004)mentioning
confidence: 99%
“…Dessa forma, observa-se que a tilápia possui um requisito específico de Se, que não pode ser atendido por alimentações regulares ou pelo meio aquático. É geralmente aceito que o selênio orgânico (selenometionina) é mais prontamente disponível do que o selênio inorgânico (por exemplo selenito de sódio) para peixes (JARAMILLO et al, 2009). Portanto, o nível de exigência dietética de selênio para tilápia-do-Nilo pode ser satisfeito usando Se orgânico a comparativamente menor nível de inclusão do que a fonte inorgânica tradicional de Se (LEE et al, 2016).…”
Section: Tabela 1 Exigências De Macrominerais E Microminerais (Por Kunclassified